Responsible use of crop protection products and Nigeria's growth enhancement support scheme. Issue 4 (19th May 2019) - Uduji, Joseph I.; Okolo-Obasi, Elda N.; Asongu, Simplice A.
ABSTRACT: This article examines the impact of the federal government of Nigeria's growth enhancement support scheme (GESS) on responsible use of crop protection products (CPPs) in rural Nigeria. Results from the logistic regressions show that GESS significantly impact on farmers' access to CPPs but does not significantly impact on farmers' knowledge and skill of CPP application, and that in several cases misuse has led to deterioration of soil fertility. Findings suggests that embracing information on recommended CPPs, dose rates, dilutions, timing, frequency of applications, and precautions should form the foundation of GESS activity on CPPs in sub-Saharan Africa.